Aortic root remodeling in bicuspid and tricuspid aortic valves—long-term results - Miyahara, Shunsuke (Indian J Thorac Cardiovasc Surg, 2019)
BACKGROUND: Root remodeling is one form of valve-preserving root replacement to treat patients with aortic regurgitation (AR) and root aneurysm. We have consistently used it for patients with and without connective tissue disease and different aortic valve morphologies. The objective of this retrospective study was to review 23 years of experience with root remodeling. METHODS AND PATIENTS: Between 10/95 and 9/2018, 1004 of 1038 root remodeling procedures were performed in patients with tricuspid (n = 589) or bicuspid (n = 414) anatomy of the aortic valve in our institution. Aortic aneurysm was present in 932 cases, 73 procedures were performed for acute aortic dissection type A. The severity of aortic regurgitation ranged from grade I to grade IV (mean 2.5 ± 0.8). RESULTS: All patients underwent root remodeling, concomitant operations were performed in 433, and cusp repair in 883 instances. Hospital mortality was 2%. Overall freedom from reoperation was 92% at 10 years and 89% at 15 years. It was 94% for tricuspid valves at 10 and 15 years, and 88% for bicuspid aortic valves at 10 years and 80% at 15 years (p = 0.003). CONCLUSION: In conclusion, root remodeling is a viable option in valve-preserving root replacement. If combined with careful assessment and, if necessary, correction of aortic valve form reproducible restoration of aortic valve function can be achieved.